A The RELATIONSHIP BETWEEN MILK HUBUNGAN PEMBERIAN SUSU DENGAN KEJADIAN REGURGITASI PADA NEONATUS DI RUANG PERINATOLOGI RSD GUNUNG JATI KOTA CIREBON: HUBUNGAN PEMBERIAN SUSU DENGAN KEJADIAN REGURGITASI PADA NEONATUS DI RUANG PERINATOLOGI RSD GUNUNG JATI KOTA CIREBON - Atma Battya,, Annesya (LPPM ITEKES Mahardika, 2023)
The number of newborns from january to march amounted to for the number of infants wwho are in the first level of 223 baby. Giving nutrition at gunung jati hospital using dot and spoon. The purpose of this research is to know the relation of way of giving milk with regurgitation incident on neonatus in the perinatologi room RSD Gunung Jati Cirebon city. This research is a descriptive correlation design with cross sectional. The population were all baby born and at level 1 (infants who have no abnomalities) from january to march amounted to 223 baby, sampling using accidental sampling numbered 30 baby. Instruments used in the from of a sheet observation. Data analysis using paired Spearman’s rho. The place of research in hospital Gunung Jati Cirebon City on May1 to May 30 2020. The test results obtaines Spearman’s rho with p-value=0.001. No relationship between Milk method with the incidence of regurgitation in the neonatus in hospital Gunung Jati Cirebon City.